PEMBERIAN RESTITUSI TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG TERHADAP PEKERJA MIGRAN INDONESIA - Wahyu Tri Hartanto; Nynda Fatmawati O (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Restitution in the context of human trafficking crimes is crucial to ensure the restoration of victims' rights that have been violated. Human trafficking is a serious crime that not only harms victims physically and mentally but also deprives them of their right to live with dignity. Restitution serves as compensation that victims are entitled to for the material and immaterial losses they have suffered. Although Indonesia has a legal framework regulating restitution, such as in the Criminal Code and Law No. 21 of 2007, its implementation still faces significant challenges, such as the difficulty in determining the value of the losses and the social stigma experienced by victims. Therefore, a sensitive approach to the victims' psychological condition, support from the government, law enforcement agencies, and non-governmental organizations (NGOs) is essential to create an environment that supports victims' recovery. In addition, a comprehensive rehabilitation program that includes psychological support, education, and job opportunities is vital. In conclusion, although the implementation of restitution faces considerable challenges, strategic measures such as increasing legal awareness, training for law enforcement, in-depth research, and multi-party cooperation can help create a fairer and more effective system in addressing human trafficking crimes.